2009
DOI: 10.1038/eye.2009.210
|View full text |Cite
|
Sign up to set email alerts
|

Learning effect in visual field testing of healthy subjects using Humphrey Matrix frequency doubling technology perimetry

Abstract: Purpose To evaluate the learning effect of frequency doubling technology (FDT) perimetry using the Humphrey Matrix perimeter in healthy subjects with no perimetric experience. Methods One eye of 28 healthy adults who had no history of visual field testing underwent three Matrix tests using 24-2 programme with full-threshold strategy. The results of the first session were compared with those of the second, and the third sessions. Learning effect was defined as an improvement at results for duration, perimetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
0
15
0
3
Order By: Relevance
“…Studies have shown that there is a learning effect and test-retest variability with FDT perimetry. [15202122] Thus, one can find visual field “improvements” if the same test is repeated on consecutive days. Pierre-Filho et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that there is a learning effect and test-retest variability with FDT perimetry. [15202122] Thus, one can find visual field “improvements” if the same test is repeated on consecutive days. Pierre-Filho et al .…”
Section: Discussionmentioning
confidence: 99%
“…Pierre-Filho et al . [20] evaluated the learning effect for the FDT Matrix perimetry using the full-threshold 24-2 strategy when the test was administered 3 times to healthy individuals who had never undergone automated perimetry and reported significant improvements in MD index with repeated testing. Finally, the results of this study may or may not hold true in a population with the visual field defects, however, this issue can be addressed in a future study in which pediatric patients with visual field defects are also recruited.…”
Section: Discussionmentioning
confidence: 99%
“…Visual field testing (perimetry) is currently the gold standard method to monitor visual loss in glaucoma. Automated Humphrey (Carl Zeiss Meditech, Dublin, CA) or Octopus (Haag-Streit) static visual field analysers are the most widely used as they are quick and less operatordependant than kinetic perimeters, with the latest threshold algorithms able to assess one eye in less than 4 minutes [24,172]. The number of points corresponding to the area of retina being tested depends on the schedule chosen, with 30-2, 24-2 and 10-2 settings indicating points 30, 24, and 10 degrees from the central point of fixation respectively at which light sensitivity is measured.…”
Section: Visual Fieldsmentioning
confidence: 99%
“…Furthermore, an obvious learning effect has been documented, suggesting more than one and preferably at least three baseline visual fields should be used to assess glaucoma severity [76,172]. For the significant number of patients with multiple comorbidities including those causing fatigue, musculoskeletal disease or dementia, it can be challenging to maintain the physical posture or the mental concentration to produce acceptable reliability indices such as low fixation losses, low false positives and low false negatives.…”
Section: Visual Fieldsmentioning
confidence: 99%
“…El estudio se desarrolló en dos visitas para el grupo de pacientes sanos en un periodo de 1 mes, con el fin de minimizar el efecto de aprendizaje en la campimetría FDT Matrix. [123][124][125] • En la primera visita se realizó la anamnesis, la exploración optométrica y oftalmológica completa, así como la medida de las pruebas estructurales y funcionales. (Apartado 2.1.7)…”
Section: Procedimientounclassified